Dipole Response of Mesoscale Eddy Formation to Monsoon Transition in the Southeast Tropical Indian Ocean - Libao Gao; Yongcan Zu; Guijun Guo; Bin Kong; Yue Fang; Guy D. Williams (Geophysical Research Letters)
Abstract The Southeast Tropical Indian Ocean (SETIO), dominated by the Indian Ocean monsoon, is an important source region for strong mesoscale eddies. To date, the impacts of the Indian Ocean monsoon on mesoscale eddies have not been clarified. Here we report on the dipole response of mesoscale eddy formation to monsoon transition in the SETIO, using satellite and reanalysis data sets. During the summer monsoon season, anticyclonic eddies are mainly concentrated north of 12°S, while cyclonic eddies are south of 12°S. This situation reverses during the winter monsoon season. We attribute this dipole feature to the oceanic perturbations and current shear during the different monsoon periods. A geographical boundary along 12°S aligns with meridional changes in eddy potential energy, which delineates the generation and direction of the newly‐formed eddies. The hot spot region, rich in eddy energy properties, tends to promote eddy formation and endurance during the monsoon periods.